HUBUNGAN ANTARA INTENSITAS BELAJAR DENGAN HASIL BELAJAR MATEMATIKA SISWA SD - Fadilatun Nikmah; Sekar Dwi Ardianti; Ika Ari Pratiwi (STKIP Subang, 2023)
Learning intensity is one of the most important things in education because if students are accustomed to increasing their learning intensity, it can affect learning outcomes that increase because students are used to learning. This study aims to see if there is a relationship between learning intensity and learning outcomes in math lessons. This study uses a quantitative approach correlation method. This research was conducted at SDN 1 Pelemkerep, Pelemkerep Village, Mayong District, Jepara Regency in June 2023. The subjects of this study were fifth grade students totaling 25 students. Data collection techniques in this study were through interviews, questionnaires, and documentation. Validation test conducted in this study is content validity. Data analysis techniques using the correlation test. The results showed that there was a positive relationship between learning intensity and student learning outcomes, which was 0.718 with a percentage of the coefficient of determination of 51,55%.